Endocrine regulation and metabolic mechanisms of osteopontin in the development and progression of osteosarcoma, metastasis and prognosis - Shao, Zhuce; Bi, Shuxiong (Frontiers in Endocrinology, 2023)
Osteosarcoma is the most common type of malignant bone tumor, occurring in adolescents and patients over 60. It has a bimodal onset and a poor prognosis, and its development has not yet been fully explained. Osteopontin (OPN) is a high protein consisting of 314 amino acid residues with a negative charge and is involved in many biological activities. OPN is not only an essential part of the regulation of the nervous system and endocrine metabolism of skeletal cells. Still, it is also involved in several other important biological activities, such as the division, transformation, and proliferation of skeletal cells and their associated cells, such as bone tumor cells, including bone marrow mesenchymal stem cells, hematopoietic stem cells, osteoblasts, and osteoclasts. Osteoblasts and osteocytes. Recent studies have shown a strong correlation between OPN and the development and progression of many skeletal diseases, such as osteosarcoma and rheumatoid arthritis. This review aims to understand the mechanisms and advances in the role of OPN as a factor in the development, progression, metastasis, and prognosis of osteosarcoma in an attempt to provide a comprehensive summary of the mechanisms by which OPN regulates osteosarcoma progression and in the hope of contributing to the advancement of osteosarcoma research and clinical treatment.